Atmospheric pressure plasma surface engineering to improve polymer matrix composite bonding - Frumosu, Lydia (Cranfield University, 2024)
This thesis explores the improvement of adhesive properties on carbon fibre reinforced epoxy composites, specifically MTM44-1, through the application of atmospheric pressure plasma (APP) treatments. The study aims to address the critical challenge of enhancing the adhesion of composite surfaces by investigating both thermal and non-thermal plasma techniques. A comprehensive analysis of plasma treatment uniformity, temperature effects, and treatment speeds has been conducted. Special emphasis is placed on the removal of silicone contamination, from mould release agents, a common barrier to effective adhesion. Current industrial approaches often struggle to fully eliminate silicone contamination, which severely limits adhesive bonding on composite surfaces. Plasma has the potential to remove silicone contamination, while also improving the surface energy, prior to adhesion. Another consideration in this study has been to the speed of plasma treatment. One of the barriers to using adhesion to bond composites in the industry is the time it takes to pre-treat surfaces prior to adhesion. This study aims to also investigate the relationship between treatment time and surface energy, especially as APP can be easily integrated into a manufacturing processes, compared to traditional plasma surface treatment. This is due to the lack of vacuum which saves time, space and often energy in the process. Various plasma generation methods were explored, including microwave, radio frequency (RF), and Dielectric Barrier Discharge (DBD), to treat the composite surfaces. This allowed for a variety of different plasma feed gases to be used including nitrogen, argon and a mixture of fluorinated gas and argon. Surface characterisation was conducted using X-ray photoelectron spectroscopy (XPS) to assess the chemical composition of the treated surfaces, while water contact angle (WCA), surface energy measurements and lap shear testing were used to evaluate the effectiveness of the treatments in promoting adhesion. The results demonstrate that plasma treatments significantly enhance the surfaceii energy of the composites by removing surface contaminants, particularly silicon containing release agents, while also altering the surface chemistry to promote better adhesive bonding. The work also evaluates the impact of processing parameters such as treatment speed and gas flow rates on surface modification efficiency and surface temperature, particularly when considering thermal radio frequency (RF) plasma.
Nichols, John - Associate Supervisor See, Tian-Long - Associate Supervisor
Keywords: Atmospheric pressure plasma; silicon contamination; composites; surface energy; adhesion; Surface Engineering; aerospace composites; non-thermal plasma; thermal plasma